Modeling Creep Fracture in Rock by Using Kelvin Discretized Virtual Internal Bond - Wangyang He; Zhennan Zhang (Advances in Civil Engineering)
Discretized virtual internal bond (DVIB) is a lattice model, which is composed of bond cells. Each bond cell has a finite number of bonds. The DVIB is used to model the creep fracture. It is done by introducing a viscous bond to the original hyperelastic DVIB. The hyperelastic bond is parallel coupled with a viscous bond together, forming a hybrid hyperelastic-Kelvin bond. The hyperelastic bond reflects the microfracture mechanism, whereas the viscous bond reflects the creep mechanism. Based on this hyperelastic-Kelvin bond, the constitutive relation of a cell is derived. The microbond parameters are calibrated based on the ideal cell approach. The simulation results suggest that this method can represent the typical features of creep and can simulate the creep fracture. The merit of this method lies in that the complicated 3D macrocreep problem is reduced to the 1D microbond creep problem. No creep law is previously derived. The macrocreep fracture behavior is the natural response of the assembly of the micro hyperelastic-Kelvin bonds.